Casual for a cause: Exploring the employment status of nursing in Australia and China - Carol Chunfeng Wang; Sadie Geraghty (Elsevier, 2017)
This paper outlines obligatory nursing education and the registration process required to become a nurse in Australia, including nurses' workload, career structure and pay. It also provides an overview of the nursing workforce in Australia, with particular reference to casual employment, and its implications. The aim of this paper is to outline the development strategies that may assist with China's increasing need for nursing education, and how changes to healthcare policy and management are required to increase the recruitment and retention of nurses in hospitals worldwide. Keywords: Australia, China, Employment, Nursing